Self-Regulated Learning of Mathematics for Teacher Prospectives in the Development of Student E-Worksheets - Kusno, Kusno; Setyaningsih, Eka (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
This research is motivated by demands for mastery of 21st-century skills as a form of educational reform in the 4.0 era. This study aims to explore the understanding and skills of the prospective mathematic teacher in the development of the student e-worksheet as a form of teacher skills in the 21st-century. A total of 27 math teacher candidates in Banyumas Regency, Central Java, Indonesia, who took part in training teaching material development, was formed into 9 Groups (G) and was given the task to develop student e- worksheet of mathematics of junior high school. Data were collected through observation, interviews, self-reflection, open questionnaires, and portfolios and analyzed using content analysis procedures by reading carefully to understand relevant themes. The coding and labeling are then carried out to find the meanings associated with the research objectives and theoretical framework. This study's results indicate that self-regulated learning of prospective mathematics education teachers in the development of student e-worksheet can encourage motivation to learn, self-confidence, experience, and determination to become professional teachers in the 21st century. From this study, an understanding and skill of the century 21can be explored from self-regulated learning during the development of student e- worksheet, namely collaboration and communication skills, problem-solving, creativity and imagination, innovation, and novelty, literacy, and leadership.